2019
DOI: 10.3390/cancers11111777
|View full text |Cite
|
Sign up to set email alerts
|

Health Status in Long-Term Survivors of Hepatoblastoma

Abstract: The aim of this study was to evaluate the health status of children cured from hepatoblastoma. Forty-five patients with hepatoblastoma treated between 1996–2014 were assessed. The recorded data included sex, age at diagnosis, disease stage, treatment methods, time since diagnosis, and the evaluation of health status domains which included performance status, growth development, hearing, cardiovascular, skeletal, gastrointestinal, genitourinary, neurological, and hematological function. There were 30 boys and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 36 publications
(40 reference statements)
1
19
0
Order By: Relevance
“…The combination of nephrotoxic chemotherapy and posttransplant medications (namely calcineurin inhibitors) likely contribute to increased renal injury, suggesting a role for closer monitoring of renal function in HB transplants and consideration of renal‐protective immunosuppression regimens, including mTOR inhibitors. The sustained impact on renal function in HB transplants is not well‐understood and requires further attention in considering long‐term health 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of nephrotoxic chemotherapy and posttransplant medications (namely calcineurin inhibitors) likely contribute to increased renal injury, suggesting a role for closer monitoring of renal function in HB transplants and consideration of renal‐protective immunosuppression regimens, including mTOR inhibitors. The sustained impact on renal function in HB transplants is not well‐understood and requires further attention in considering long‐term health 25 …”
Section: Discussionmentioning
confidence: 99%
“…The sustained impact on renal function in HB transplants is not wellunderstood and requires further attention in considering longterm health. 25 The lack of centralized pathology review in this study limits our ability to draw definitive conclusions regarding the effect of HB histologic subtypes on outcomes following LT. As previously described, pure fetal histology with low mitoses was associated with excellent survival. 11,26,27 The poorer EFS for epithelial tumors compared to mixed epithelial/mesenchymal tumors has not been These limitations must be considered when interpreting survival outcomes.…”
Section: Ta B L E 1 Definitions Of Transplant-associated Outcomesmentioning
confidence: 96%
“…The mainstay of most chemotherapy regimens has been cisplatin and doxorubicin, which are dose-limited due to renal, auditory, and cardiac toxicities. [9][10][11][12][13] Other agents such as carboplatin, ifosfamide, and etoposide have also been used in various combinations with minimal improvement in EFS. 4,14 Because of the rarity of HB, traditional phase I and phase II clinical trial mechanisms have generally been unsuccessful in identifying novel effective agents.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy is an essential part of treatment for this high‐risk patient group. The mainstay of most chemotherapy regimens has been cisplatin and doxorubicin, which are dose‐limited due to renal, auditory, and cardiac toxicities 9–13 . Other agents such as carboplatin, ifosfamide, and etoposide have also been used in various combinations with minimal improvement in EFS 4,14 .…”
Section: Introductionmentioning
confidence: 99%
“…11 In a study from Poland of 45 patients with HB identified at the authors' institution, a SMN rate of 6.6% was reported. 12 In another Japanese study of 361 patients with HB treated on the Japanese Study Group for Paediatric Liver Tumours-2 trial protocol, the authors found an increased risk of SMNs with a higher pirarubicin dose and a lower age at diagnosis. 13 Chemotherapeutic agents used in HB treatment are known to be associated with an increased risk of the development of SMNs.…”
mentioning
confidence: 98%